17. ANXIETY IN POST-CAESAREAN MOTHERS AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2024 AND RELATED FACTORS (Tạp chí Y học Cộng đồng, 2024)
Objectives: This study aims to describe the anxiety status of post-caesarean mothers at Vinmec Times City International Hospital, Hanoi, in 2024, and analyze related factors.Methods: A cross-sectional descriptive study was conducted with 302 post-caesarean mothers. Data were collected from February to April 2024 through interviews using a structured questionnaire that included demographic information and the DASS-21 scale to assess anxiety levels.Results: The rate of anxiety among post-caesarean mothers was 27.2%, ranging from mild to very severe levels. Factors such as first-time childbirth, family pressure, sleep disorders, and the child’s health status showed significant associations with maternal anxiety levels.Conclusion: Post-caesarean anxiety is an issue requiring attention and support within the hospital. Appropriate psychological interventions, especially for mothers facing social pressure or having children with health complications, are essential to safeguard maternal mental health and promote optimal child development.
Keywords: DASS-21; anxiety; post-caesarean mothers; Vinmec